Deciding to Leave Care Is Not Dropout: The Emerging Adult Perspective. Issue 4 (October 2022) - Green, Shawna Marie; Boothroyd, Roger A.; Armstrong, Mary; Lubotsky Levin, Bruce; Martinez Tyson, Dinorah; Massey, Oliver
Emerging adults discontinue behavioral health treatment at rates ranging from 30% to 50%. This study explored dropout using semi-structured interviews ( N = 20). Participants were engaged in a group therapy program, Healthy Transitions. Findings revealed the lack of therapeutic relationship and logistical issues such as cost, transportation, and conflicting work schedules contributed to dropout. Participants indicated that alleviating logistical barriers and feeling a connection to their peers and group leader prevented dropout. This program was free, transportation was provided, and sessions were in the evening. Participants expressed peer educators made them feel less judged and/or stigmatized than a one-on-one therapy appointment. These findings reinforce logistical issues and lack of a therapeutic relationship contribute to dropout and highlight the benefits of flexible scheduling and reinforce the importance of a therapeutic relationship in preventing dropout.